Numerical investigation on the effect of channelled and unchannelled screens on smoke contamination in atriums upper balconies with open upstand - Mutafi M.; Nasif M.; Pao W.; Ismail F. (EDP Sciences, 2023)
Computational fluid dynamics; Computer software; Contamination; Fluid dynamics; Fire compartments; Fire dynamic simulators; New correlations; Numerical investigations; Smoke